UJI BIOLARVASIDA EKSTRAK METANOL DAUN JERUK NIPIS (Citrus aurantifolia) TERHADAP LARVA NYAMUK Aedes aegypti L. - Siska Musiam; Maya Armianti; Aditya Maulana Perdana Putra (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Aedes aegypti L. mosquito is a vector of Dengue Hemorrhagic Fever (DBD) transmission. The control of Aedes aegypti L. mosquito vector by using larvasida is done as an effort to overcome DBD. In this research, the activity test of methanol extract of lime leaves (Citrus aurantifolia) has been done as Aedes aegypti L. mosquito biolarvacide. The concentration of lime leaf extract methanol (Citrus aurantifolia) used in this research were 0,1%, 0,2%; 0,3%; and 0,4%. Temephos 1% was used as a positive control and tap water as a negative control. Each treatment used 20 larvae of Aedes aegypti L. Instar III and replicated four times. The result of SPSS analysis stated that there is influence of concentration on death number of test larvae, where at concentration 0,3%, 0,4% and positive control Temephos 1% did not show the meaningful differences of death larva test number. The obtained LC50 values are at intervals of 0,089% to 0,123% with an estimated concentration of 0.108%.